Clinical and Translational Considerations for Understanding Depression and Anxiety in Patients with Inflammatory Bowel Disease - Ashley M. Sidebottom; Tina G. Rodriguez; Jordan E. Karpin; David T. Rubin (Gastroenterology Research and Practice)
Depression and anxiety are comorbidities of inflammatory bowel disease (IBD). Though previous studies have proposed a relationship between anxiety, depression, and IBD, causality and directionality are largely unknown. Current and future research in these areas is aimed at exploring the biological underpinnings of this relationship, specifically pertaining to small molecule metabolism, such as tryptophan. Tryptophan is acquired through the diet and is the precursor to several vital bioactive metabolites including the hormone melatonin, the neurotransmitter serotonin, and vitamin B3. In this review, we discuss previous findings relating mental health comorbidities with IBD and underline ongoing research of tryptophan catabolite analysis.